Intensive Initial Oral Anticoagulation and Shorter Heparin Treatment in Deep Vein Thrombosis - Schulman, Sam; Lockner, Dieter; Bergström, Kurt; Blombäck, Margareta (Thrombosis and Haemostasis, 1984)
In order to investigate whether a more intensive initial oral anticoagulation still would be safe and effective, we performed a prospective randomized study in patients with deep vein thrombosis. They received either the conventional regimen of oral anticoagulation (“low-dose”) and heparin or a more intense oral anticoagulation (“high-dose”) with a shorter period of heparin treatment.In the first part of the study 129 patients were randomized. The “low-dose” group reached a stable therapeutic prothrombin complex (PT)-level after 4.3 and the “high-dose” group after 3.3 days. Heparin was discontinued after 6.0 and 5.0 days respectively. There was no difference in significant hemorrhage between the groups, and no clinical signs of progression of the thrombosis.In the second part of the study another 40 patients were randomized, followed with coagulation factor II, VII, IX and X and with repeated venograms. A stable therapeutic PT-level was achieved after 4.4 (“low-dose”) and 3.7 (“high-dose”) days, and heparin was discontinued after 5.4 and 4.4 days respectively. There were no clinical hemorrhages, the activity of the coagulation factors had dropped to the same level in both groups at the time when heparin was discontinued and no thromboembolic complications occurred.Our oral anticoagulation regimen with heparin treatment for an average of 4.4-5 days seems safe and reduces in-patient costs.
Keywords: Deep-vein thrombosis; Oral anticoagulation; Warfarin; Initial therapy; Coagulation factors